2019
DOI: 10.1093/cid/ciz406
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Rapid Species Identification From Positive Blood Cultures With Same-day Phenotypic Antimicrobial Susceptibility Testing on the Management and Outcome of Bloodstream Infections

Abstract: Background Timely availability of microbiological results from positive blood cultures is essential to enable early pathogen-directed therapy. The Accelerate Pheno system (ADX) is a novel technology using fluorescence in situ hybridization for rapid species identification (ID) and morphokinetic bacterial analysis for phenotypic antimicrobial susceptibility testing (AST), with promising results. Yet the impact of this technology on clinical management and patient outcome remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 32 publications
11
38
0
Order By: Relevance
“…We observed that providers were more willing to de-escalate empirical antimicrobial therapy after final AST (provided by AXDX) as opposed to after ID and resistance gene results alone, primarily due to the possibility of undetected resistance with genotypic testing. This is similar to that for other institutions that have shown time from Gram stain to ID and AST, time to optimal therapy, time to step-down antimicrobial therapy, and length of stay outcomes through AXDX utilization ( 14 , 15 ). This earlier de-escalation of antimicrobial therapy in Enterobacteriaceae bloodstream infections can significantly help decrease Clostridioides difficile infection rates, as recently reported in literature ( 16 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We observed that providers were more willing to de-escalate empirical antimicrobial therapy after final AST (provided by AXDX) as opposed to after ID and resistance gene results alone, primarily due to the possibility of undetected resistance with genotypic testing. This is similar to that for other institutions that have shown time from Gram stain to ID and AST, time to optimal therapy, time to step-down antimicrobial therapy, and length of stay outcomes through AXDX utilization ( 14 , 15 ). This earlier de-escalation of antimicrobial therapy in Enterobacteriaceae bloodstream infections can significantly help decrease Clostridioides difficile infection rates, as recently reported in literature ( 16 ).…”
Section: Discussionsupporting
confidence: 82%
“…This is similar to other institutions that have shown time from gram stain to ID and AST, time to optimal therapy, time to step-down antimicrobial therapy, and length of stay outcomes through AXDX utilization. [17][18] This earlier de-escalation of antimicrobial therapy in Enterobacteriaceae bloodstream infections can significantly help decrease Clostridioides difficile infection rates as recently reported in literature. 19 on October 29, 2020 by guest http://aac.asm.org/…”
Section: Discussionmentioning
confidence: 67%
“…Real-world impact on patient outcomes has been examined in small studies that included Gram-negative bacteremia and showed improved time to optimal antimicrobial therapy but no change in clinical outcomes or antibiotic consumption (24)(25)(26). Selection of positive blood cultures from the daytime shift only and a dedicated team of investigators with full ASP intervention may explain shorter intervals for antibiotic change.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether this rapid turnaround time (TAT) translates into more favorable clinical outcomes remains to be determined. 46 , 47 …”
Section: Rapid Direct Phenotypic Antimicrobial Susceptibility Testimentioning
confidence: 99%